Caracterização, germinação e conservação de sementes de visgueiro (Parkia pendula (Wild.) Benth. ex Walpers) e de maravilha (Caesalpinia pulcherrima (L.) Sw) - Camara, Celene de Albuquerque (2007)
The use of native and exotic species with characteristics for reconstitution and the use of quality seeds are responsible factors for the success in the programs of reforestation of degraded areas. This work aimed the morphometric characterization of fruits and seeds of visgueiro (Parkia pendula (Wild.) Benth. ex Walpers) and maravilha (Caesalpinia pulcherrima (L.) Sw.), and the study of germination capacity and storage conditions. Ripe fruits of both species were picked of located plants in Maceió and Rio Largo, state of Alagoas, in the period of october 2005 to january 2006. In the seeds the humidity degree was determined and accomplished the morphometric characterization. It was evaluated, for both species, the effect of different germination temperatures (15ºC, 25ºC, 30ºC, 35ºC, 40ºC, 45ºC and 50ºC), different drying periods (0, 72, 120, 168, 216 hours for visgueiro and 0, 24, 48, 72, 120, 168 hours for maravilha) under temperature of 40ºC ± 5ºC, three types of packings (a leaf of paper bag of the type "Kraft", four leaves of the same paper and glass flasks tightly closed) and two atmospheres for the storage (normal of laboratory, without humidity control and temperature and controlled atmosphere, camera dries - 20ºC and 45% UR). For maravilha, it was evaluated, also, the effect of three treatments for superation of the dormancy (intact seeds, mechanically seeds escarificated and submerged seeds in water distilled by 24 hours). For all experiments, there were four repetitions of 25 seeds for treatment. The data were submitted to the variance analysis and the averages compared by the Tukey test, to 5% of probability. For ends of statistical analysis the germination data were transformed in arcsen v x/100. The fruit of P. pendula presents, on mean, 16,0 cm of length, 20,9 of width mm and 4,2 mm of thickness and the seeds, of format ellipsoidal, they are endowed with pleurograma, they measure about 10,1 mm of length, 4,9 mm of width and 3,1 mm of thickness and they possess embryo of the axial and lineal type. The temperatures of 25ºC and 30ºC provide the largest percentage values and germination speed and the drying for 72 hours promoted induction and/or intensification of the hardness in the seeds. The fruit of C. pendula presents, on mean, 10,1 cm of length, 19,0 mm of width and 7,0 mm of thickness and the seeds, of oblong-oval format, they measure about 9,6 mm of length, 7,3 mm of width and 3,2 mm of thickness and they possess embryo of the axial and lineal type. The mechanical scarification of the tegument and the temperatures of 25ºC and 35ºC promoted larger percentage and germination speed at the first 24 hours of drying promoted reduction in the speed of germination of the seeds. Starting from a month of storage, in both species, there was decrease of the speed independently of the packing and the storage conditions used.